2021
DOI: 10.3390/molecules26051487
|View full text |Cite
|
Sign up to set email alerts
|

Tea as a Source of Biologically Active Compounds in the Human Diet

Abstract: Due to the different levels of bioactive compounds in tea reported in the literature, the aim of this study was to determine whether commercially available leaf teas could be an important source of phenolics and selected minerals (copper, manganese, iron, zinc, magnesium, calcium, sodium, potassium) and if the differences in the content of these components between various types of tea are significant. It was found that both the amount of these compounds in tea and the antioxidant activity of tea infusions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…On the other hand, herb extract also contributed significantly ( p ≤ .05) to the sodium content of DDs which might be due to the presence of sodium in a ginger root, that is, 38.96 μg/g (Ogbuewu et al, 2014). Tea extract concentration affects potassium content of DDs inversely (Table 3) owing to its contribution in tea, that is, 30,362 μg/ 100 ml (Klepacka et al, 2021). However, the potassium content increased with an increase in herb extract concentration because ginger is a good source of essential micronutrients such as potassium, magnesium, copper, and manganese (Bhatt et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, herb extract also contributed significantly ( p ≤ .05) to the sodium content of DDs which might be due to the presence of sodium in a ginger root, that is, 38.96 μg/g (Ogbuewu et al, 2014). Tea extract concentration affects potassium content of DDs inversely (Table 3) owing to its contribution in tea, that is, 30,362 μg/ 100 ml (Klepacka et al, 2021). However, the potassium content increased with an increase in herb extract concentration because ginger is a good source of essential micronutrients such as potassium, magnesium, copper, and manganese (Bhatt et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Red and green teas are rich sources of antioxidants, particularly flavonoids. 16,17 A study using Ethiopian tea leaves demonstrated that level of L-theanine in green teas are higher than black ones by > 48 mg/g and by < 31 mg/g of dried aqueous extract, respectively. 18…”
Section: Discussionmentioning
confidence: 99%
“…Tea is one of the most popular beverages consumed around the globe and prepared from the leaves of Camellia sinensis. The beneficial effect of tea on human health is primarily due to its high antioxidant activity, which results mainly from the presence of tannins and catechins (epicatechin, epigallocatechin), as well as their derivatives (epicatechin gallate and epigallocatechin gallate) [ 37 , 38 , 39 ]. Seeds are another product in addition to the leaves of the tea plant; they are the source of vegetable oil, an important plant oil due to its high content of unsaturated fatty acids, especially essential linoleic acid.…”
Section: Other Unconventional Uses Of Polyphenols Lipophilizationmentioning
confidence: 99%